Overcoming Difficulties in Memorizing Arabic Vocabulary Through Direct Methods and Teaching Aids - Ana Sofia; Najma Azzahra (Nurul Jadid University, 2026)
Vocabulary memorization remains a significant challenge in Arabic language learning because students often struggle to retain and use newly learned words effectively. This study aimed to investigate how the implementation of direct methods and teaching aids could overcome students’ difficulties in memorizing Arabic vocabulary. The study employed a qualitative descriptive design involving one Arabic language teacher and 20 students in an intensive Arabic learning class. Data were collected through classroom observations, semi-structured interviews, and documentation and analyzed using data condensation, data reduction, data display, and conclusion drawing. The findings revealed that the direct method improved vocabulary retention through contextual language exposure, while teaching aids increased students’ engagement and comprehension through visual and concrete representations. The integration of both strategies reduced students’ dependence on translation, increased confidence in using Arabic vocabulary, and facilitated meaningful vocabulary acquisition. The novelty of this study lies in combining direct methods and teaching aids within a unified instructional framework. These findings suggest that Arabic language teachers should integrate communicative and visual learning strategies to improve vocabulary mastery.